Analyzing the impact of working expectations on intention to apply in Indonesia: A study on Gen Z college graduate - Inta Hartaningtyas Rani; Jara Hardiyanti Jalih; Lestari Adhi Widyowati (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2023)
The expansion of businesses is limited in enhancing the workforce because recruiting personnel requires significant effort and financial resources. The returns on these businesses should be assessed while decreasing the expenses associated with recurrent needs. Therefore, this study aimed to analyze the correlation between the employment expectations of soon-to-be college graduates, who constituted a significant portion of the workforce, and their inclination. Factors such as organizational attractiveness, person-organization fit, and social media usage were examined as mediating variables. The advancement of the theory of planned behavior was also investigated, particularly in explaining how organizations shape the behavior of prospective employees based on expectations. Using the structural equation model (SEM) method, the data were examined on intention to apply among 350 Indonesian college students on the brink of graduation (middle year of Gen Z). The results showed that working expectations influenced intention to apply for a job, through direct impact and partial mediation. According to the descriptive statistics, a company's top three priorities for respondents were health insurance, a coaching manager, and job security.